Assessment of the usage and effectiveness of intermittent preventive treatment and insecticide-treated nets on the indicators of malaria among pregnant women attending antenatal care in the Buea Health District, Cameroon. (December 2016) - Fokam, Eric; Ngimuh, Leonard; Anchang-Kimbi, Judith; Wanji, Samuel
Abstract Background Malaria in pregnancy is an immense public health problem with at least 50 million pregnant women living in malaria endemic areas. To prevent malaria and its complications in pregnancy the World Health Organization recommends the use of intermittent preventive treatment sulfadoxine–pyrimethamine (IPTp-SP), the use of insecticide-treated nets (ITNs), and effective case management. In most malaria endemic countries in Africa, 40 % of pregnant women sleep under ITNs. In Cameroon, about 90 % of pregnant women receive the first dose of SP, while 64 % take the complete dose. Following the 2011 mass-campaign of free distribution of ITNs coupled with routine ANC distribution of ITN and adoption of IPTp in Cameroon, little has been done to assess the effectiveness of both interventions outside of Yaoundé, the capital city. This study sought to assess the usage and effectiveness of IPTp-SP and ITNs on malaria in pregnancy. Methods The research was a cross-sectional hospital-based study that included 410 pregnant women attending antenatal clinics in the Buea Health District. Capillary blood samples were collected to check malaria parasite by microscopy and haemoglobin levels by microhaematocrit technique. Results A prevalence of 13.4 and 41.7 % was detected for malaria and anaemia, respectively. The Overall coverage of ITN was 32.4 % while that of ITPp was 63.2 %. Malaria prevalence was least (7.2 %) amongst women using both IPTp-SP and ITN while those with no intervention had the highest malaria prevalence of 18.6 % (χ2 = 6.188; P = 0.103). Of the women with malaria, 12.73 % were using ITN and had taken at least one dose of SP, 38.18 % had taken at least one dose IPTp only, 10.91 % were using only ITN and 38.18 % were not using any preventive measure. There was a difference in anaemia status within the different intervention groups (χ2 = 8.673; P = 0.034). Pregnant women using both interventions were less associated to malaria (OR = 0.341, 95 % CI = 0.138–0.841) compared to those using only one control method. Conclusion Repeated doses of SP in combination with ITN use are effective in reducing malaria parasitaemia and improving haemoglobin level of pregnant women.